Assessing Meat-eating: An Emancipation Attempt - Katsilakis, Athanasios (Conatus - Journal of Philosophy, 2018)
The illusion that by transcending and defying existing social stereotypes we form freely our opinions and attitudes prevents us from questioning multidimensional phenomena. This article addresses the morality of such a social behavior. In this paper I will discuss two arguments in favor of creophage, the first assuming its 'naturalness' and the second evoking our species' superiority, I will conclude with the view that we ought to be morally concerned about the interests of farmed animals, and that widespread animal suffering should be criticized and rejected as unethical.